Two Intellectual Upheavals Induced by the Digital Transformation - Bautier, Roger (Bobcatsss, 2023)
The Enlightenment movement has widely disseminated the conception of a citizen who, in order to be enlightened, must master reading and writing. This conception appears as a fundamental reference for the functioning of the public sphere. But this functioning is affected by the new writing and reading practices induced by the digital transformation. This is why the objective of this poster is to highlight two complementary aspects of digital transformation that have major consequences on digital literacy and digital culture in general. First, the decontextualisation, suspension and reconstruction of meaning. As it gives the means to favor methods that suspend the immediate comprehension of a text, computing easily appears as a methodological guarantee. This feature is particularly visible in the analysis of cultural data on a large scale, which leads to the delinearization of the text because the tools used traverse the entire corpus and produce results most often in the form of lists or of diagrams. Knowledge is therefore not going to be based on reading texts, but on processing corpuses. Second, the unseen formatting of communication and thought. A computer's operating system is inaccessible to the average user, whereas anyone who can read is able to access printed text. At the same time, the concealment of procedures allows a form of transparency to emerge, or even to be brought to the fore, which must manifest itself in the interfaces. But the conditions of communication in a digital environment are largely determined by actors who possess technical or economic capacities. These capacities will impose both the possibilities and the limits of the mode of communication. As a result, the form of texts is constrained by the requirements of computerization, requirements which tend to privilege precisely what is computable.